Holocene palaeoenvironmental and human settlement evolution in the southern margin of the Salpi lagoon, Tavoliere coastal plain (Apulia, Southern Italy). (10th May 2023) - Susini, Davide; Vignola, Cristiano; Goffredo, Roberto; Totten, Darian Marie; Masi, Alessia; Smedile, Alessandra; De Martini, Paolo Marco; Cinti, Francesca Romana; Sadori, Laura; Forti, Luca; Fiorentino, Girolamo; Sposato, Andrea; et al.
Abstract: This study aims to understand the relationship between the palaeoenvironmental evolution of the southern margin of the Salpi lagoon (Tavoliere coastal plain, Apulia, Italy) and the development of settlements on its shores during the last part of the Holocene (Late Northgrippian to Late Meghalayan) to complement recent archaeological investigations at the site of pre-Roman Salpia Vetus, Roman Salapia and Medieval Salpi . Micropalaeontological, palynological, and sedimentological analyses were conducted on a total of ten drilled cores, revealing local and regional events. Facies and micropalaeontological analyses show that the lagoon was partially connected to the sea between 6.2 ka BP and 3.1 ka BP. Between 3.1 ka BP and 2.4 ka BP, the area was characterised by marshes and swamps with restricted brackish lagoon conditions and permanent freshwater input. After 2.4 ka BP, the continuous freshwater influx from the major rivers of the coastal plain determined the progradation of the floodplain and the closure of the lagoon, with the formation of the two coastal lakes of Lago Salso (north) and Lago Salpi (south). Pollen data show the expansion of halophytic herbs under local brackish conditions during the Early Meghalayan and the continuous spread of dryland herbs consistent with the closure of the basin. The alluvial plain progradation during the Late Meghalayan allowed the intensive exploitation of the area and the development of a highly anthropogenic landscape. The development of the settlements of pre-Roman Salpia Vetus, Roman Salapia, and Medieval Salpi was mainly determined by the insalubrious condition of the surrounding marshes, due to the reduction in water depth and oscillations in salinity.